2011
DOI: 10.1007/s10584-011-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

The identification of distinct patterns in California temperature trends

Abstract: Regional changes in California surface temperatures over the last 80 years are analyzed using station data from the US Historical Climate Network and the National Weather Service Cooperative Network. Statistical analyses using annual and seasonal temperature data over the last 80 years show distinctly different spatial and temporal patterns in trends of maximum temperature (Tmax) compared to trends of minimum temperature (Tmin). For trends computed between 1918 and 2006, the rate of warming in Tmin is greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 31 publications
11
59
0
Order By: Relevance
“…In line with previous studies that report increasing trends in temperature across California [27,28,[73][74][75], this study identifies general upward trends in watershed-wide minimum temperature and average temperature across annual, seasonal and monthly scales. Particularly, the trend in the minimum temperature is more consistent (across study watersheds) and significant (in terms of increasing rate).…”
Section: Discussionsupporting
confidence: 89%
“…In line with previous studies that report increasing trends in temperature across California [27,28,[73][74][75], this study identifies general upward trends in watershed-wide minimum temperature and average temperature across annual, seasonal and monthly scales. Particularly, the trend in the minimum temperature is more consistent (across study watersheds) and significant (in terms of increasing rate).…”
Section: Discussionsupporting
confidence: 89%
“…By contrast, typically only 5%-15% of stations had negative trends irrespective of starting period, reiterating the results of Mote (2003). Similar to previous global and regional studies, minimum temperatures increased more than maximum temperature from 1920 to 2012, whereas increases in maximum and minimum temperature were comparable for the last half century (e.g., Vose et al 2005;Cordero et al 2011).…”
Section: B Individual Stationssupporting
confidence: 85%
“…Observations show an accelerated warming rate with linear trends for the 1970-2012 and 1980-2012 time periods of approximately 0.28C decade 21 (Fig. 1b), similar to that seen globally (e.g., Trenberth et al 2007, p. 253) and in other regions (e.g., Cordero et al 2011). Structural differences between these datasets do not appear to significantly alter long-term temperature trends for the PNW.…”
Section: A Regional Averagessupporting
confidence: 75%
“…This is of particular concern because T min is increasing significantly faster than T max in California (Cordero et al 2011). Several studies have combined climate model output with historically observed temperature-yield relationships to conclude that by mid-to late century, most current locations of perennial specialty crop production in California will no longer be climatically suitable for many key crops (Lobell et al 2006;Baldocchi and Wong 2008;Luedeling et al 2009; T sensitivity refers to the relative magnitude (1=low, 4=high) of negative impacts on the crop from increased temperatures Data from USDA NASS 2012 Statistical Bulletins #1032, 1033, and 1043 a Wine grapes were assigned a T max sensitivity of 3; raisin and table grapes were assigned a T max sensitivity of 1; and they were calculated as two independent crop types and Field 2011; Hannah et al 2013;Baldocchi and Waller 2014).…”
Section: Previous Work On Specialty Crops and Climate Changementioning
confidence: 99%